Randomized Double-blind Placebo-controlled Trial of Celecoxib for Oral Mucositis in Patients Receiving Radiation Therapy for Head and Neck Cancer - Lalla, Rajesh V. (Oral Oncol, 2014)
OBJECTIVES: Oral mucositis (OM) is a painful complication of radiation therapy (RT) for head and neck cancer (H&NC). OM can compromise nutrition, require opioid analgesics and hospitalization for pain control, and lead to treatment interruptions. Based on the role of inflammatory pathways in OM pathogenesis, we investigated effect of cyclooxygenase-2 (COX-2) inhibition on severity and morbidity of OM. METHODS: In this double-blind placebo-controlled trial, 40 H&NC patients were randomized to daily use of 200 mg celecoxib or placebo, for the duration of RT. Clinical OM, normalcy of diet, pain scores, and analgesic use were assessed 2–3 times/week by blinded investigators during the 6–7 week RT period, using validated scales. RESULTS: Twenty subjects were randomized to each arm, which were similar with respect to tumor location, radiation dose, and concomitant chemotherapy. In both arms, mucositis and pain scores increased over course of RT. Intention-to-treat analyses demonstrated no significant difference in mean Oral Mucositis Assessment Scale (OMAS) scores at 5000 cGy (primary endpoint). There was also no difference between the two arms in mean OMAS scores over the period of RT, mean worst pain scores, mean normalcy of diet scores, or mean daily opioid medication use in IV morphine equivalents. There were no adverse events attributed to celecoxib use. CONCLUSIONS: Daily use of a selective COX-2 inhibitor, during period of RT for H&NC, did not reduce the severity of clinical OM, pain, dietary compromise or use of opioid analgesics. These findings also have implications for celecoxib use in H&NC treatment regimens (NCT00698204).